Weed Interference in Semi-Erect and Semi-Prostate Cowpea Cultivars - CASTRO,T.S. (2019)
ABSTRACT: This study aimed to determine weed interference periods in semi-erect and semi-prostrate cowpea cultivars. Two simultaneous experiments were conducted with the cowpea cultivars BRS Guariba (semi-erect) and BRS Aracê (semi-prostrate). The experimental design was a randomized block design with four replications in a 7 × 2 factorial scheme, seven periods × two weed management (control and coexistence). Control and coexistence periods consisted of 0, 0-8, 0-16, 0-24, 0-32, 0-45, and 0-60 days after emergence (DAE) for the semi-erect cultivar and 0, 0-8, 0-16, 0-24, 0-32, 0-45, and 0-64 DAE for the semi-prostrate cultivar. Competition throughout the cycle reduced productivity by up to 39.81% for BRS Guariba and 37.27% for BRS Aracê. The cultivars BRS Guariba and BRS Aracê presented critical period of interference prevention of 9 to 41 DAE and 15 to 32 DAE, respectively. The semi-prostrate cultivar BRS Aracê was more competitive with weeds, requiring a shorter control period to express maximum productivity.